Microbiological Hygiene Quality of Thermal Muds: A Pilot Study in Pelotherapy Facilities of the Euganean Thermal District (NE Italy) - Tatjana Baldovin (International Journal of Environmental Research and Public Health, 2020)
Evaluation of hygienic aspects of thermal mud microbiology is still neglected. This study evaluates the microbiological hygiene quality of thermal muds, providing a comprehensive assessment of the whole mud cultivation chain. Maturing mud, peloid and used mud samples were collected twice in a year from 30 SPAs of the Euganean Thermal District, NE Italy. Samples were processed with an ad hoc laboratory method. The following indicator parameters were assessed: Total Count at 22, 37 and 55 °C; total coliforms; Escherichia coli; enterococci; Staphylococcus aureus; Pseudomonas aeruginosa; sulfite-reducing clostridia; dermatophytes. Statistical significance of differences between the two sampling campaigns and correlation between temperature and indicator parameters were evaluated. One-hundred eighty samples were analyzed. Widespread presence of environmental species was found, as well as hints of possible microorganism transfer from the patient’s skin to the mud. Proper setting of thermal water temperature resulted critical, in terms of hygienic quality. Although optimal maturation should be granted (thermal water at 30–42 °C), a pasteurization step at 60–65 °C is strongly recommended to sanitize peloids before pelotherapy. Facilities re-using thermal muds should also implement a regeneration step at ≥65 °C. Core evaluation of thermal mud hygienic quality could encompass the following guidelines: absence (i.e., 0 colony forming units (CFU)/g) of E. coli, P. aeruginosa, S. aureus and dermatophytes.